Magnesium-lithium alloy surface treatment liquid as well as preparation method and application thereof

The high-temperature saponification film layer is formed through the surface treatment liquid of magnesium lithium alloy, which solves the oxidation and ablation problem of magnesium lithium alloy materials during high-temperature stamping, and realizes the stability and economy of high-temperature stamping, which is suitable for industrial applications.

CN119121206APending Publication Date: 2024-12-13JIANGMEN REACH FINE CHEM IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411130528.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Prior Art When the magnesium lithium alloy material is stamped at high temperature, the surface of the material is easily oxidized, ablated or powdered, resulting in poor physical characteristics and structural performance. The existing solutions such as the low cost of phosphated film treatment but fail to achieve the best. Stamping temperature requirements, and high cost of anodized film treatment is not conducive to large-scale industrial applications.

Method used

Using magnesium lithium alloy surface treatment liquid, including advanced fatty acid salts, alkyl alcohol polyoxyethylene sulfate salts and triethanolamine, a high temperature-resistant and dense saponified film layer is formed through mechanical polishing, oxidation resistance and drying processes. , increase the stamping temperature to 380-400℃ to avoid oxidative ablation.

Benefits of technology

The oxidation resistance of magnesium lithium alloy materials during high temperature stamping is better than that of anodic oxidation film, and the cost is lower than that of anodic oxidation film. It is suitable for large-scale industrial applications, and has a simple process and low cost, which is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004997688810000141
    Figure BDA0004997688810000141
Patent Text Reader

Abstract

The invention provides a magnesium-lithium alloy surface treatment liquid as well as a preparation method and application thereof. The magnesium-lithium alloy surface treatment liquid comprises the following components: higher fatty acid salt, alkyl alcohol polyoxyethylene sulfate and triethanolamine. According to the magnesium-lithium alloy surface treatment liquid, the raw materials are easy to obtain, the preparation process is simple, and the cost is low. And the formed film layer is high in oxidation-resistant temperature, stable in quality and convenient for batch production. By using the magnesium-lithium alloy surface treatment liquid disclosed by the invention, not only is the problem of insufficient high-temperature oxidation resistance of a phosphating film treatment process solved, but also the problem of too high cost of an anodic oxide film treatment process is solved, and the magnesium-lithium alloy surface treatment liquid is beneficial to realizing high-temperature punch forming. The invention further provides a preparation method and application of the magnesium-lithium alloy surface treatment liquid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of magnesium-lithium alloy surface treatment, and in particular relates to a magnesium-lithium alloy surface treatment liquid and a preparation method and application thereof. Background Art

[0002] Magnesium alloy is known as the green metal structural material of the 21st century. It has low density, high specific strength and specific stiffness, and excellent damping, cutting and casting properties. It has been increasingly widely used in many fields such as automobile manufacturing, aerospace industry, and electronic communications. Magnesium-lithium alloy is the lightest metal structural material among the magnesium alloys studied so far. It not only has various advantages of magnesium alloys, but also has outstanding shock absorption performance, strong resistance to high-energy particle penetration, good mechanical processing and cold forming performance, etc. It can better meet the needs of modern society for lightweight materials and will have broader application prospects in the fields of aerospace and communications, weapon equipment manufacturing, and "3C" products.

[0003] In order to meet the actual application needs of magnesium-lithium alloy materials in various fields, the original bars or plates of magnesium-lithium alloy materials need to be processed into products of various shapes by stamping or forging, and then different surface treatments are performed according to the needs to achieve the functional effects of corrosion protection and decoration. The current processing method of magnesium-lithium alloy products mainly adopts high-temperature stamping. The different conditions and parameters of stamping will not only affect the physical properties and structural properties of the material itself, but also affect the quality of subsequent surface treatment. Among them, the stamping temperature is particularly critical to the material properties and product quality, because magnesium-lithium alloy has the best ductility at a temperature of 380°C, and it is easier to stamp and form products with complex shapes, avoiding problems such as material strain, cracking, and metal segregation. The molded products have the advantages of good quality, stability, and high yield rate. However, when the original rods or plates of magnesium-lithium alloy materials (without any surface treatment) are heated to 320-340°C, the surface of the material will be oxidized, burned, blackened, and powdered, which not only deteriorates the physical properties and structural performance of the material and makes it unqualified, but also affects the quality and yield of subsequent surface treatments such as electroplating and painting, thus limiting the increase in stamping temperature and creating a contradiction.

[0004] In order to solve the problem of ablation or powdering of the material surface caused by increasing the stamping temperature, the existing solutions are: 1. Using a lower temperature (300-320℃) for stamping, although it can avoid the problem of oxidation and ablation of the material surface, due to the low temperature, the ductility of the material is poor. For products with more complex shapes, cracks or metal segregation problems appear at the chamfers, which cannot be effectively solved. Therefore, this method is only suitable for products with simple shapes and low requirements for quality, performance and yield. 2. Before the hot stamping process, the surface of the original bar or plate of the magnesium-lithium alloy is chemically oxidized to form a layer of phosphating film. This film layer has a good high-temperature oxidation protection effect, so that when the stamping temperature can be increased to 350-360℃, there is no oxidation and ablation on the surface. At this time, the material has good ductility, and for products with simple shapes, it can fully meet the quality and performance requirements; However, when stamping products with complex shapes, there are still a small number of cracks and unstable quality at the chamfers. Therefore, this method can meet the requirements of most products, and the increased process cost is not much, but it still cannot meet the requirements of products with higher precision and quality requirements. 3. Before the hot stamping process, the surface of the original bar or plate of the magnesium-lithium alloy is anodized to form a layer of high-temperature resistant oxide film. This film layer has better high-temperature oxidation protection, so that when the stamping temperature can be increased to 380-390°C, there is no oxidation and ablation on the surface. At this time, the material has the best ductility and can meet the requirements of all products. The quality of the molded products is good and the yield rate is high. Although this method can well solve the current problem of ablation or powdering of the material surface caused by increasing the stamping temperature, the high cost of anodizing treatment increases the entire manufacturing cost exponentially, which is not conducive to large-scale industrial applications. Therefore, in view of the shortcomings of the existing methods for solving the problem of oxidation and ablation of the material surface due to high temperature during high-temperature stamping of magnesium-lithium alloy materials, a new reagent and process still need to be developed. Summary of the invention

[0005] The present invention aims to solve at least one of the above technical problems existing in the prior art. To this end, the present invention provides a magnesium-lithium alloy surface treatment solution to solve the problem of oxidation of the material surface due to high temperature.

[0006] The invention also provides a method for preparing a magnesium-lithium alloy surface treatment solution.

[0007] The present invention also provides a method for high temperature oxidation treatment of the surface of magnesium-lithium alloy

[0008] The first aspect of the present invention provides a magnesium-lithium alloy surface treatment solution, the components of which include higher fatty acid salts, alkyl alcohol polyoxyethylene sulfate salts and triethanolamine.

[0009] The purpose of the present invention is to address the shortcomings of existing methods for solving the problem of oxidation and ablation of the surface of magnesium-lithium alloy materials due to high temperature stamping. Specifically:

[0010] Although the phosphating film treatment process is low-cost, it fails to meet the requirements of the optimal stamping temperature; although the anodized film treatment process can meet the requirements of the optimal stamping temperature, the cost is doubled, which is not conducive to large-scale industrial applications. To this end, the present invention provides a magnesium-lithium alloy surface treatment liquid, which is used to perform special surface treatment on the surface of the original rod or plate of the magnesium-lithium alloy. The process flow includes three main steps: mechanical polishing treatment, oxidation resistance treatment, and drying treatment. After being treated with the treatment liquid, a high-temperature resistant and dense saponification film layer is formed on the surface of the magnesium-lithium alloy material, so that when the stamping temperature of the magnesium-lithium alloy material can be increased to 380-400°C, oxidation and ablation will not occur on the surface, and the temperature resistance is better than that of the anodized film. Using the magnesium-lithium alloy surface treatment liquid of the present invention, the process cost is lower than that of the phosphating film treatment process, and is significantly lower than that of the anodized film treatment process, which is conducive to large-scale industrial applications.

[0011] The magnesium-lithium alloy surface treatment liquid of the present invention has readily available raw materials, a simple preparation process and low cost. The formed film layer has a high oxidation resistance temperature, stable quality and is convenient for mass production. The use of the magnesium-lithium alloy surface treatment liquid of the present invention not only solves the problem of insufficient high-temperature oxidation resistance of the phosphating film treatment process, but also solves the problem of excessively high cost of the anodized film treatment process, which is conducive to high-temperature stamping forming of magnesium-lithium alloy.

[0012] In the magnesium-lithium alloy surface treatment solution, the role of the higher fatty acid salt is to react with magnesium ions on the surface of the magnesium-lithium alloy to form a magnesium oleate saponification film layer.

[0013] The role of alkyl alcohol polyoxyethylene sulfate is to work with the main film-forming agent to make the soap film layer on the surface thicker and denser, and better resistant to high temperature oxidation.

[0014] Triethanolamine is used as a buffer to adjust and buffer the pH value and stabilize the pH value of the drug solution.

[0015] According to some embodiments of the present invention, the higher fatty acid salt includes at least one of sodium oleate and sodium palmitate.

[0016] According to some embodiments of the present invention, the alkyl alcohol polyoxyethylene sulfate salt includes at least one of alkyl alcohol polyoxyethylene ether sulfate sodium salt and nonylphenol polyoxyethylene ether sulfate sodium salt.

[0017] According to some embodiments of the present invention, per liter of the magnesium-lithium alloy surface treatment solution, the components include:

[0018] Higher fatty acid salts: 3g~10g,

[0019] Alkyl alcohol polyoxyethylene sulfate: 3g~10g,

[0020] Triethanolamine: 2g~8g.

[0021] The balance is water.

[0022] According to some embodiments of the present invention, per liter of the magnesium-lithium alloy surface treatment solution, the components include:

[0023] Higher fatty acid salts: 5g~7g,

[0024] Alkyl alcohol polyoxyethylene sulfate: 5g~7g,

[0025] Triethanolamine: 4g~6g.

[0026] The second aspect of the present invention provides a method for preparing the magnesium-lithium alloy surface treatment solution described in the first aspect of the present invention, wherein the components are mixed uniformly according to a proportion.

[0027] A technical solution in the method for preparing a magnesium-lithium alloy surface treatment solution of the present invention has at least the following beneficial effects:

[0028] The preparation method of the magnesium-lithium alloy surface treatment liquid of the present invention does not require expensive equipment and complex process control, has undemanding reaction conditions, has readily available raw materials, has low production costs, and is easy to industrialize.

[0029] The third aspect of the present invention provides a method for high temperature oxidation resistant treatment of the surface of a magnesium-lithium alloy, the method comprising the step of subjecting a workpiece to be treated to oxidation resistance treatment in the magnesium-lithium alloy surface treatment solution as described in the first aspect of the present invention.

[0030] The method for high temperature resistant oxidation treatment of magnesium-lithium alloy surface of the present invention aims to solve the shortcomings of existing methods for solving the problem of oxidation and ablation of material surface due to high temperature when magnesium-lithium alloy material is stamped and formed at high temperature. Specifically, the phosphating film treatment process, although low in cost, fails to meet the optimal stamping temperature requirements; the anodized film treatment process, although able to meet the optimal stamping temperature requirements, increases the cost exponentially, which is not conducive to large-scale industrial applications.

[0031] To this end, the present invention provides a method for high-temperature resistant oxidation treatment of the surface of a magnesium-lithium alloy, which is to perform special surface treatment on the surface of the original rod or plate of the magnesium-lithium alloy using the magnesium-lithium alloy surface treatment liquid of the present invention. The process flow may include three main steps: mechanical polishing treatment, oxidation resistance treatment, and drying treatment. After being treated by this method, a high-temperature resistant and dense saponification film layer is formed on the surface of the magnesium-lithium alloy material, so that when the stamping temperature of the magnesium-lithium alloy material can be increased to 380-400°C, there is no oxidation and ablation phenomenon on the surface, and the temperature resistance is better than that of the anodized film. However, its process cost is lower than that of the phosphating film treatment process, and is significantly lower than that of the anodized film treatment process, which is conducive to large-scale industrial applications.

[0032] The method for high temperature oxidation treatment of the surface of magnesium-lithium alloy of the present invention has the advantages of simple process, low cost, high oxidation resistance temperature of the film layer, stable quality and convenience for mass production. It not only solves the problem of insufficient high temperature oxidation resistance of the phosphating film treatment process, but also solves the problem of high cost of the anodized film treatment process. It is the best solution for the current high temperature stamping forming method of magnesium-lithium alloy.

[0033] After the oxidation resistance treatment, a dense saponification film layer is formed on the surface of the magnesium-lithium alloy. Under high temperature conditions, it can effectively block the oxidation and ablation of oxygen and the magnesium-lithium alloy material, thereby playing a role in high temperature oxidation resistance.

[0034] According to some embodiments of the present invention, during the oxidation resistance treatment, the pH of the solution is 10-12.

[0035] If the pH is lower than 10, the material will corrode and the oxidation resistance will be reduced; if the pH is greater than 12, a thick magnesium lithium oxide film will be formed, reducing the oxidation resistance.

[0036] According to some embodiments of the present invention, the temperature of the oxidation resistance treatment is 50°C to 70°C.

[0037] According to some embodiments of the present invention, the time of the oxidation resistance treatment is 20s to 60s.

[0038] According to some embodiments of the present invention, the method further comprises a step of polishing the workpiece to be treated before the oxidation resistance treatment.

[0039] Polishing can make the surface of magnesium-lithium alloy material flat and smooth, remove the thick oxide film on the surface, make the metal on the surface of the material active, which is beneficial to the subsequent film formation and film quality.

[0040] Polishing conditions can be:

[0041] Sandpaper mesh: 1000 mesh

[0042] Grinding wheel speed: 1000 rpm,

[0043] Temperature: 20-30℃,

[0044] Time: 3-6 minutes.

[0045] According to some embodiments of the present invention, the method further comprises the step of drying the workpiece to be treated after the oxidation resistance treatment.

[0046] Drying can make the surface fully dry and form a dense saponification film layer.

[0047] According to some embodiments of the present invention, the drying temperature is 70°C to 80°C.

[0048] According to some embodiments of the present invention, the drying time is 15s to 20s. DETAILED DESCRIPTION

[0049] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0050] In a first aspect, in some embodiments of the present invention, a magnesium-lithium alloy surface treatment solution is provided, the components of which include higher fatty acid salts, alkyl alcohol polyoxyethylene sulfate salts and triethanolamine.

[0051] The purpose of the present invention is to address the shortcomings of existing methods for solving the problem of oxidation and ablation of the surface of magnesium-lithium alloy materials due to high temperature stamping. Specifically:

[0052] Although the phosphating film treatment process is low-cost, it fails to meet the requirements of the optimal stamping temperature; although the anodized film treatment process can meet the requirements of the optimal stamping temperature, the cost is doubled, which is not conducive to large-scale industrial applications. To this end, the present invention provides a magnesium-lithium alloy surface treatment liquid, which is used to perform special surface treatment on the surface of the original rod or plate of the magnesium-lithium alloy. The process flow includes three main steps: mechanical polishing treatment, oxidation resistance treatment, and drying treatment. After being treated with the treatment liquid, a high-temperature resistant and dense saponification film layer is formed on the surface of the magnesium-lithium alloy material, so that when the stamping temperature of the magnesium-lithium alloy material can be increased to 380-400°C, oxidation and ablation will not occur on the surface, and the temperature resistance is better than that of the anodized film. Using the magnesium-lithium alloy surface treatment liquid of the present invention, the process cost is lower than that of the phosphating film treatment process, and is significantly lower than that of the anodized film treatment process, which is conducive to large-scale industrial applications.

[0053] The magnesium-lithium alloy surface treatment liquid of the present invention has readily available raw materials, a simple preparation process and low cost. The formed film layer has a high oxidation resistance temperature, stable quality and is convenient for mass production. The use of the magnesium-lithium alloy surface treatment liquid of the present invention not only solves the problem of insufficient high-temperature oxidation resistance of the phosphating film treatment process, but also solves the problem of excessively high cost of the anodized film treatment process, which is conducive to high-temperature stamping forming of magnesium-lithium alloy.

[0054] In the magnesium-lithium alloy surface treatment solution, the role of the higher fatty acid salt is to react with magnesium ions on the surface of the magnesium-lithium alloy to form a magnesium oleate saponification film layer.

[0055] The role of alkyl alcohol polyoxyethylene sulfate is to work with the main film-forming agent to make the soap film layer on the surface thicker and denser, and better resistant to high temperature oxidation.

[0056] Triethanolamine is used as a buffer to adjust and buffer the pH value and stabilize the pH value of the drug solution.

[0057] In combination with the first aspect, in some embodiments of the present invention, the higher fatty acid salt includes at least one of sodium oleate and sodium palmitate.

[0058] In combination with the first aspect, in some embodiments of the present invention, the alkyl alcohol polyoxyethylene sulfate salt includes at least one of alkyl alcohol polyoxyethylene ether sulfate sodium salt and nonylphenol polyoxyethylene ether sulfate sodium salt.

[0059] In combination with the first aspect, in some embodiments of the present invention, the components in each liter of magnesium-lithium alloy surface treatment liquid include:

[0060] Higher fatty acid salts: 3g~10g,

[0061] Alkyl alcohol polyoxyethylene sulfate: 3g~10g,

[0062] Triethanolamine: 2g~8g.

[0063] The balance is water.

[0064] In combination with the first aspect, in some embodiments of the present invention, the components in each liter of magnesium-lithium alloy surface treatment liquid include:

[0065] Higher fatty acid salts: 5g~7g,

[0066] Alkyl alcohol polyoxyethylene sulfate: 5g~7g,

[0067] Triethanolamine: 4g~6g.

[0068] In a second aspect, some embodiments of the present invention provide a method for preparing the magnesium-lithium alloy surface treatment solution of the first aspect of the present invention, wherein the components are mixed uniformly according to a proportion.

[0069] It can be understood that the preparation method of the magnesium-lithium alloy surface treatment liquid of the present invention does not require expensive equipment and complex process control, the reaction conditions are not harsh, the raw materials are easily available, the production cost is low, and it is easy to industrialize production.

[0070] In a third aspect, some embodiments of the present invention provide a method for high temperature oxidation resistant treatment of the surface of a magnesium-lithium alloy, the method comprising the step of subjecting a workpiece to be treated to oxidation resistance treatment in a magnesium-lithium alloy surface treatment solution as described in the first aspect of the present invention.

[0071] The method for high temperature resistant oxidation treatment of magnesium-lithium alloy surface of the present invention aims to solve the shortcomings of existing methods for solving the problem of oxidation and ablation of material surface due to high temperature when magnesium-lithium alloy material is stamped and formed at high temperature. Specifically, the phosphating film treatment process, although low in cost, fails to meet the optimal stamping temperature requirements; the anodized film treatment process, although able to meet the optimal stamping temperature requirements, increases the cost exponentially, which is not conducive to large-scale industrial applications.

[0072] To this end, the present invention provides a method for high-temperature resistant oxidation treatment of the surface of a magnesium-lithium alloy, which is to perform special surface treatment on the surface of the original rod or plate of the magnesium-lithium alloy using the magnesium-lithium alloy surface treatment liquid of the present invention. The process flow may include three main steps: mechanical polishing treatment, oxidation resistance treatment, and drying treatment. After being treated by this method, a high-temperature resistant and dense saponification film layer is formed on the surface of the magnesium-lithium alloy material, so that when the stamping temperature of the magnesium-lithium alloy material can be increased to 380-400°C, there is no oxidation and ablation phenomenon on the surface, and the temperature resistance is better than that of the anodized film. However, its process cost is lower than that of the phosphating film treatment process, and is significantly lower than that of the anodized film treatment process, which is conducive to large-scale industrial applications.

[0073] The method for high temperature oxidation treatment of the surface of magnesium-lithium alloy of the present invention has the advantages of simple process, low cost, high oxidation resistance temperature of the film layer, stable quality and convenience for mass production. It not only solves the problem of insufficient high temperature oxidation resistance of the phosphating film treatment process, but also solves the problem of high cost of the anodized film treatment process. It is the best solution for the current high temperature stamping forming method of magnesium-lithium alloy.

[0074] After the oxidation resistance treatment, a dense saponification film layer is formed on the surface of the magnesium-lithium alloy. Under high temperature conditions, it can effectively block the oxidation and ablation of oxygen and the magnesium-lithium alloy material, thereby playing a role in high temperature oxidation resistance.

[0075] In combination with the third aspect, in some embodiments of the present invention, during the oxidation resistance treatment, the pH of the solution is 10-12.

[0076] In combination with the third aspect, in some embodiments of the present invention, the temperature of the oxidation resistance treatment is 50°C to 70°C.

[0077] In combination with the third aspect, in some embodiments of the present invention, the time of the oxidation resistance treatment is 20s to 60s.

[0078] In combination with the third aspect, in some embodiments of the present invention, the method further comprises a step of polishing the workpiece to be treated before the oxidation resistance treatment.

[0079] Polishing can make the surface of magnesium-lithium alloy material flat and smooth, remove the thick oxide film on the surface, make the metal on the surface of the material active, which is beneficial to the subsequent film formation and film quality.

[0080] Polishing conditions can be:

[0081] Sandpaper mesh: 1000 mesh,

[0082] Grinding wheel speed: 1000 rpm,

[0083] Temperature: 20-30℃,

[0084] Time: 3-6 minutes.

[0085] In combination with the third aspect, in some embodiments of the present invention, the method further comprises the step of drying the workpiece to be treated after the oxidation resistance treatment.

[0086] Drying can make the surface fully dry and form a dense saponification film layer.

[0087] In combination with the third aspect, in some embodiments of the present invention, the drying temperature is 70°C to 80°C.

[0088] In combination with the third aspect, in some embodiments of the present invention, the drying time is 15s to 20s.

[0089] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0090] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0091] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.

[0092] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.

[0093] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0094] Example 1

[0095] First, a magnesium-lithium alloy surface treatment solution was prepared, the components of which were:

[0096] Sodium oleate (CAS: 143-19-1): 6g / L,

[0097] Alkyl alcohol polyoxyethylene ether sulfate sodium salt (CAS: 68991-38-3): 6g / L,

[0098] Triethanolamine (CAS: 102-71-6): 5g / L,

[0099] The balance is pure water.

[0100] The specific preparation method is to prepare 1L of liquid medicine as an example:

[0101] 1. Take 700mL of pure water and heat it to 50℃;

[0102] 2. While stirring, add the three weighed drugs in sequence (the order of adding materials does not matter);

[0103] 3. After the drug is completely dissolved, use a pH meter to test the pH value of the solution and confirm that it is between 10-12;

[0104] 4. Add pure water to 1L, stir well and it is ready for use.

[0105] Example 2

[0106] First, a magnesium-lithium alloy surface treatment solution was prepared, the components of which were:

[0107] Sodium palmitate (CAS: 408-35-5): 6g / L,

[0108] Alkyl alcohol polyoxyethylene ether sulfate sodium salt (CAS: 68991-38-3): 6g / L,

[0109] Triethanolamine (CAS: 102-71-6): 5g / L,

[0110] The balance is pure water.

[0111] The specific preparation method is the same as that in Example 1.

[0112] Example 3

[0113] First, a magnesium-lithium alloy surface treatment solution was prepared, the components of which were:

[0114] Sodium oleate (CAS: 143-19-1): 6g / L,

[0115] Nonylphenol polyoxyethylene ether sulfate sodium salt (CAS: 9014-90-8): 6g / L,

[0116] Triethanolamine (CAS: 102-71-6): 5g / L,

[0117] The balance is pure water.

[0118] The specific preparation method is the same as that in Example 1.

[0119] Example 4

[0120] First, a magnesium-lithium alloy surface treatment solution was prepared, the components of which were:

[0121] Sodium palmitate (CAS: 408-35-5): 6g / L,

[0122] Nonylphenol polyoxyethylene ether sulfate sodium salt (CAS: 9014-90-8): 6g / L,

[0123] Triethanolamine (CAS: 102-71-6): 5g / L,

[0124] The balance is pure water.

[0125] The specific preparation method is the same as that in Example 1.

[0126] Test Materials

[0127] LZ-91 magnesium-lithium alloy sheet, size: 320mm×240mm, thickness: 0.4-0.6mm. It will be formed by high-temperature stamping and then surface treated before being applied to a certain brand of 13-inch notebook shell.

[0128] The composition of LZ-91 magnesium-lithium alloy sheet is shown in Table 1.

[0129] Table 1

[0130] element Mg Li Zn Si Mn other content(%) Balance 8.0-10.0 0.5-1.0 <0.2 <0.2 <0.3

[0131] Implementation of the process

[0132] The sequence is: mechanical water polishing → pure water washing → oxidation resistance treatment → drying → cooling → high temperature oxidation resistance testing.

[0133] The operating conditions of mechanical water polishing are:

[0134] Sandpaper mesh: 1000 mesh,

[0135] Grinding wheel speed: 1000 rpm,

[0136] Temperature: 25℃,

[0137] Time: 4min.

[0138] The operating conditions of oxidation resistance treatment are:

[0139] pH: 11,

[0140] Temperature: 60℃,

[0141] Time: 40s.

[0142] The drying conditions are:

[0143] Temperature: 75℃,

[0144] Time: 8min.

[0145] High temperature oxidation resistance test method

[0146] Equipment: Sanhua Mechanical Electric Heating Oven, with a range of 0-450°C and an error of ±2°C.

[0147] Heat the electric oven to the set temperature, then put the workpiece to be tested into the oven, close the oven door, and when the temperature in the oven rises to the set temperature again, the timer will automatically start timing, and after 20 minutes of constant temperature, the heating and heat preservation will automatically stop, and then take out the sample and place it in the room air to cool naturally to room temperature. Observe whether the surface of the sample is oxidized, ablated, blackened, or powdered and detached. If any of these phenomena occur, it is unqualified, otherwise it is qualified.

[0148] Comparative Example 1

[0149] There is no passivation treatment, and the process flow is: mechanical water polishing → pure water washing → alkali neutralization → pure water washing → drying → cooling → high temperature oxidation resistance testing.

[0150] Among them, the conditions for alkali neutralization are:

[0151] Sodium hydroxide: 100g / L; Temperature: 50-60℃; Time: 1min; Stirring: Still.

[0152] Comparative Example 2

[0153] It is a phosphating film treatment process, and the specific process flow is: mechanical automatic water polishing → pure water washing → acid etching → pure water washing → surface adjustment → pure water washing → phosphating film treatment → pure water washing → drying → cooling → high temperature oxidation resistance detection.

[0154] The conditions for acid etching are:

[0155] Citric acid: 20g / L; Tartaric acid: 10g / L; Temperature: 40-50℃; Time: 1min; Stirring: Still.

[0156] The conditions for table adjustment are:

[0157] Sodium hydroxide: 100g / L; Sodium nitrate: 4g / L; Temperature: 50-60℃; Time: 1min; Stirring: Still.

[0158] The conditions for phosphating film treatment are:

[0159] Phosphoric acid: 20g / L; Sodium hydroxide: 30g / L; Calcium nitrate: 5g / L; Temperature: 50-60℃; Time: 3min; Stirring: Still; pH value: 2.2-2.8; Film thickness: 3-7μm.

[0160] Except for the above three steps, other steps and conditions are the same as those in the embodiment.

[0161] Comparative Example 3

[0162] It is an anodic oxide film treatment process, and the process flow is: mechanical automatic water polishing → pure water washing → alkaline etching → pure water washing → anodic oxidation treatment → pure water washing → drying → cooling → high temperature oxidation resistance detection.

[0163] The conditions for alkaline etching are:

[0164] Sodium hydroxide: 100g / L; Sodium carbonate: 20g / L; Temperature: 50-60℃; Time: 1min; Stirring: Still.

[0165] The conditions for anodizing treatment are:

[0166] Potassium hydroxide: 80g / L; Sodium metasilicate: 50g / L; Aluminum hydroxide: 20g / L; Temperature: 20-30℃, Cathode plate: Stainless steel (304); Anode current density: 1.5-2.5A / dm 2 ; DC voltage: 65-70V, 7-10min in the first stage; 80-90V, 10-20min in the second stage; film thickness: 15-20μm.

[0167] Comparative Example 4

[0168] The difference from Example 1 is that the treatment liquid does not contain sodium salt of alkyl alcohol polyoxyethylene ether sulfate.

[0169] Comparative Example 5

[0170] The difference from Example 1 is that the treatment liquid does not contain sodium oleate.

[0171] The treatment liquids of Examples 1 to 4 were tested according to the process of mechanical water polishing → pure water washing → oxidation resistance treatment → drying → cooling → high temperature oxidation resistance test, and compared with the comparative example. The results are shown in Table 2.

[0172] Table 2

[0173]

[0174] It can be seen from the results in Table 2 that the treatment solution of the present invention has the best effect in the high temperature oxidation resistance test comparison results after treating the magnesium-lithium alloy. The treatment solution of the present invention has a simple process flow and low cost, and meets the requirements of industrial application.

[0175] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A magnesium-lithium alloy surface treatment solution, characterized in that: The components include higher fatty acid salts, alkyl alcohol polyoxyethylene sulfate salts and triethanolamine.

2. The magnesium-lithium alloy surface treatment solution according to claim 1, characterized in that: The higher fatty acid salt includes at least one of sodium oleate and sodium palmitate.

3. The magnesium-lithium alloy surface treatment solution according to claim 1, characterized in that: The alkyl alcohol polyoxyethylene sulfate salt includes at least one of alkyl alcohol polyoxyethylene ether sulfate sodium salt and nonylphenol polyoxyethylene ether sulfate sodium salt.

4. The magnesium-lithium alloy surface treatment solution according to any one of claims 1 to 3, characterized in that: The components of each liter of the magnesium-lithium alloy surface treatment solution include: Higher fatty acid salts: 3g~10g, Alkyl alcohol polyoxyethylene sulfate: 3g~10g, Triethanolamine: 2g~8g.

5. The magnesium-lithium alloy surface treatment solution according to claim 4, characterized in that: The components of each liter of the magnesium-lithium alloy surface treatment solution include: Higher fatty acid salts: 5g~7g, Alkyl alcohol polyoxyethylene sulfate: 5g~7g, Triethanolamine: 4g~6g.

6. A method for preparing a magnesium-lithium alloy surface treatment solution as claimed in any one of claims 1 to 5, characterized in that: Mix all components according to the ratio.

7. A method for high temperature oxidation treatment of magnesium-lithium alloy surface, characterized in that: The method comprises the step of subjecting the workpiece to be treated to an oxidation resistance treatment in the magnesium-lithium alloy surface treatment solution according to any one of claims 1 to 5.

8. The method according to claim 7, characterized in that The temperature of the oxidation resistance treatment is 50° C. to 70° C.; and / or the time of the oxidation resistance treatment is 20s to 60s.

9. The method according to claim 7, characterized in that: The method further comprises the step of polishing the workpiece to be treated before the oxidation resistance treatment.

10. The method according to claim 7, characterized in that The method further comprises the step of drying the workpiece to be treated after the oxidation resistance treatment.